DETERMINANTS FACTOR ANALYSYS OF UNDERPRICING ON INITIAL PUBLIC OFFERING AT INDONESIA STOCK EXCHANGE - Ardhiani Fadila; Muhammad Zilal Hamzah; Pardomuan Sihombing (Universitas Trisakti, 2015)
Under pricing is phenomenon of IPO which often happened in capital market and have been examined by researchers in many countries. This study aims to analyze the determinant factors of under pricing. This data is collected from some stocks at Indonesia Stock Exchange, especial for non-financial sector company which performed initial public offering period 2010-2014.The samples used were 75 companies that were taken through purposive sampling. Independent variables in this study are Macro Economic Data, Financial Data and Non-Financial Data.The result shows that all independent variables simultaneously have a significance correlation toward under pricing. Its prove that the rate of inflation has effect on determining IPOs price which impact on profit companies also stock prices. While non-financial information (proxies by underwriter reputation) has a negative correlation toward the degree of under pricing. Its mean that a good performance of underwriter can decrease the IPOs under pricing.